2022
DOI: 10.3390/ijerph19031784
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors in Adolescent Suicidal Behaviour: A Network Analysis

Abstract: Given that death by suicide continues to rank among the top three causes of death during adolescence, new psychological models may contribute critical insight towards understanding the complex interactions between risk and protective factors in suicidal behaviour. The main objective of this study was to analyse the psychological network structure of suicidal behaviour and putative risk and protective factors in school-aged adolescents. Methods: Stratified random cluster sampling was performed. The final sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 63 publications
3
28
1
6
Order By: Relevance
“…Previous analyses in this study cohort only explored the relationship between suicidal ideation and SDQ prosocial subscale scores, finding no statistically significant associations [ 31 ]. Similarly, no clear association between prosocial behaviours and suicidality have been reported in Spanish adolescents [ 62 , 63 ]; our paper extends this finding to Indigenous youth in Australia.…”
Section: Discussionsupporting
confidence: 81%
“…Previous analyses in this study cohort only explored the relationship between suicidal ideation and SDQ prosocial subscale scores, finding no statistically significant associations [ 31 ]. Similarly, no clear association between prosocial behaviours and suicidality have been reported in Spanish adolescents [ 62 , 63 ]; our paper extends this finding to Indigenous youth in Australia.…”
Section: Discussionsupporting
confidence: 81%
“…(2,18) The results of one study showed that bullying, cyberbullying and peer problems are related, thus indicating a direct and positive relationship with suicidal behavior. (19) As far as family relationships are concerned, they can assume the role of risk or protective factors. Difficulties in relationships, communication, lack of affection and support, fights, physical and verbal violence are present in dysfunctional family relationships.…”
Section: Discussionmentioning
confidence: 99%
“…(22) In this sense, evidence identifies that social vulnerability in adolescents is related to negative aspects, especially those associated with involvement with drugs, loss of guaranteed rights and opportunities in the areas of education, health and social protection, with situations of violence, whether domestic or communal, and child labor. (19) Despite still being treated as taboo, issues related to psychological suffering and mental disorders, especially in the adolescent phase, have been taking place in the school environment and require rapid and early interventions, in order to prevent these young people from developing risk behaviors that culminate in suicide. For example, a multicenter European study, which conducted an intervention entitled Young Mental Health Aware Program, which aimed to prevent suicide at school for students at risk.The program was effective in reducing the number of suicide attempts and severe suicidal ideation in school adolescents in the long term (12 months).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that in addition to non-fatal self-harm (Mars et al, 2019), factors that decrease fear of death, pain or injury make the transition easier from suicidal ideation to action (for review, see Klonsky et al, 2018). In general, worldwide evidence suggests that important risk factors for suicide among adolescents or late school-aged children include mental illnesses, suicide attempt history (Sanchez-Gistau et al, 2013), self-esteem and bullying, personality traits, family issues, and means of committing suicide (for review, see Bilsen, 2018;Fonseca-Pedrero et al, 2022).…”
Section: Discussionmentioning
confidence: 99%